ANALISIS DETERMINAN FRAUD DIAMOND TERHADAP DETEKSI FRAUDULENT FINANCIAL STATEMENT - Yudha Adnovaldi; Wibowo Wibowo (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2019)
The study aims to obtain empirical evidence regarding financial statement fraud based on the theory of fraud diamond. In this study, the independent variable is financial stability, external pressure, financial target, nature of industry, ineffective monitoring, rationalization, and capability variable. The study uses earnings management to investigate the potential of financial statement fraud. Earnings management is measured by F-Score indicator. Sample are 32 manufacturing companies which are listed on the Indonesia Stock Exchange (IDX) in 2015-2017. The result shows that only external pressure variable which is proxied by leverage ratio and nature of the industry variable which is proxied by obsolete inventory account that has significantly influences to detect the potential of financial statement fraud. Meanwhile financial stability which is proxied by changes in total assets ratio, financial targets which is proxied by ROA ratio, ineffective monitoring which is proxied by number of independent commissioners ratio, rationalization variable which is proxied by change in auditor, and capability variable which is proxied by change in directors do not affect to detect the potential of financial statement fraud.